Periodontal diseases and adverse pregnancy outcomes. Present and future - Bobetsis Yiorgos A; Ide Mark; Gürsoy Mervi; Madianos Phoebus N (United States, 2025)
For more than two decades the possible association between periodontal diseases and adverse pregnancy outcomes has been extensively evaluated. Numerous observational, intervention, and mechanistic studies have offered valuable information on this topic. However, several methodologic limitations still remain a significant drawback for this set of investigations, and therefore safe conclusions are not always easy to draw. Unfortunately, despite the strong recommendations from the scientific community, recent studies have not sufficiently addressed these limitations and, therefore, have not significantly altered our perception regarding the association between periodontal disease and adverse pregnancy outcomes. This review briefly describes the established knowledge and gives emphasis to the current literature. In addition, owing to the main theme of this Periodontology 2000 volume, special reference will be made regarding the results from European studies on periodontal disease and adverse pregnancy outcomes. Finally, new strategies and research guidelines are proposed in order to move on to the next level of evidence that will help connect the theoretical knowledge with meaningful clinical interventions that will benefit our pregnant patients and their offspring.